The Use of Models as a Form of Written Feedback to Secondary School Pupils of English - Martínez Esteban, Noelia; Roca de Larios, Julio (International Journal of English Studies, 2010)
The present study investigated how noticing is related to composing and subsequent feedback processing in individual and collaborative EFL writing. Participants were Spanish secondary school pupils at a lowintermediate proficiency level who completed a three-stage writing task that included writing a picture-based story (Stage 1), comparing their written texts with two native-speaker models (Stage 2), and attempting subsequent revisions (Stage 3). The results indicate that the students noticed mainly lexical problems at the writing stage but could only find a few solutions to those problems in the models provided. However, the comparison with the models allowed them, especially those who wrote collaborativelly, to notice a large number of features related to the content of the pictures and the linguistic means used to express that content. They were also found to incorporate a reasonable number in subsequent revisions. A number of implications from these findings for research and pedagogy are suggested.